If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(2x + -1) = 3 Reorder the terms: 2x(-1 + 2x) = 3 (-1 * 2x + 2x * 2x) = 3 (-2x + 4x2) = 3 Solving -2x + 4x2 = 3 Solving for variable 'x'. Reorder the terms: -3 + -2x + 4x2 = 3 + -3 Combine like terms: 3 + -3 = 0 -3 + -2x + 4x2 = 0 Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -0.75 + -0.5x + x2 = 0 Move the constant term to the right: Add '0.75' to each side of the equation. -0.75 + -0.5x + 0.75 + x2 = 0 + 0.75 Reorder the terms: -0.75 + 0.75 + -0.5x + x2 = 0 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + -0.5x + x2 = 0 + 0.75 -0.5x + x2 = 0 + 0.75 Combine like terms: 0 + 0.75 = 0.75 -0.5x + x2 = 0.75 The x term is -0.5x. Take half its coefficient (-0.25). Square it (0.0625) and add it to both sides. Add '0.0625' to each side of the equation. -0.5x + 0.0625 + x2 = 0.75 + 0.0625 Reorder the terms: 0.0625 + -0.5x + x2 = 0.75 + 0.0625 Combine like terms: 0.75 + 0.0625 = 0.8125 0.0625 + -0.5x + x2 = 0.8125 Factor a perfect square on the left side: (x + -0.25)(x + -0.25) = 0.8125 Calculate the square root of the right side: 0.901387819 Break this problem into two subproblems by setting (x + -0.25) equal to 0.901387819 and -0.901387819.Subproblem 1
x + -0.25 = 0.901387819 Simplifying x + -0.25 = 0.901387819 Reorder the terms: -0.25 + x = 0.901387819 Solving -0.25 + x = 0.901387819 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.25' to each side of the equation. -0.25 + 0.25 + x = 0.901387819 + 0.25 Combine like terms: -0.25 + 0.25 = 0.00 0.00 + x = 0.901387819 + 0.25 x = 0.901387819 + 0.25 Combine like terms: 0.901387819 + 0.25 = 1.151387819 x = 1.151387819 Simplifying x = 1.151387819Subproblem 2
x + -0.25 = -0.901387819 Simplifying x + -0.25 = -0.901387819 Reorder the terms: -0.25 + x = -0.901387819 Solving -0.25 + x = -0.901387819 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.25' to each side of the equation. -0.25 + 0.25 + x = -0.901387819 + 0.25 Combine like terms: -0.25 + 0.25 = 0.00 0.00 + x = -0.901387819 + 0.25 x = -0.901387819 + 0.25 Combine like terms: -0.901387819 + 0.25 = -0.651387819 x = -0.651387819 Simplifying x = -0.651387819Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.151387819, -0.651387819}
| 1-6x+5x=-6 | | -540+13.50=1500 | | 16=2(s-16)+8 | | 2-k=1 | | x(x-2)(x-6)=96 | | 15=3(d+1) | | 3n^2-2n+9=2 | | 4ab^2-3ab^2=1 | | 7n+3n-6n+2=18 | | (2)=(2)(b+(1)) | | (2x+24)+(4x-36)+6x=180 | | 13f=9 | | (2)=(2)(bt(1)) | | 2x+24+4x-36+6x=180 | | 15x-15=113+x | | p=4x+15 | | J-17=(3) | | 3x-10=62 | | 3x-12=15x+24 | | K+20=0 | | 2(g+7)=20 | | 34=0.4(p+22) | | 5n+12+3n=2n+30 | | 12/2=x/15 | | D-3=(2) | | r^3+3r=5 | | 3x-12=15x+8 | | 7x+1.5x=32560 | | 27(n-1)=3(6) | | 3r+13r=-16 | | (x-8)2+(y+2)2=49 | | 27n-1=18 |